PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM KELAS V SEKOLAH DASAR - Mustika, Shiska; Sabri,, Tahmid; Margiyati, K.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to analyze the influence of the use of problem-based learning strategies to student learning outcomes in science learning VB SD Negeri 01 Pontianak Selatan class. Form of research used in this research is quasi experiment with research design one group pre test - post test designe. Based on the statistic calculation, the average of pre-test is 58,34 and the average post-test is 79,71, obtained tcount 83,63 at significance stage Î± = 5% obtained ttable equal to 2,042 and effect size (ES) equal to 2.35 (high criteria) so that it can be concluded that the learning with problem based learning strategy gives a high influence on the learning outcomes of science students of grade V SD Negeri 01 Pontianak Selatan.Keywords: problem based learning, learning outcomes, Natural Science